Nutrition's Limited Impact on Adolescent Menstrual Regularity: Dampak Terbatas Nutrisi pada Keteraturan Menstruasi Remaja - Medita Chaidar Zuhrotul Maulida medita; Yanik Purwanti (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigated the relationship between nutritional status and menstrual cycle regularity in female adolescents at SMAN 4 Blitar. Using a cross-sectional analytic survey with 47 randomly selected respondents, data were collected through observation and interviews in January 2023. The Chi-Square test results showed no significant relationship (p = 0.16) between nutritional status and menstrual cycle regularity. The findings suggest that while most adolescents had regular cycles and normal nutrition, factors like stress, activity, and diet may also play a role. Educators should continue menstrual health education, and students should maintain balanced nutrition and healthy habits. Highlight: No significant link between nutrition and menstrual regularity (p = 0.16). Most teens had normal cycles and nutrition. Stress, activity, diet affect menstrual regularity. Keyword: Menstrual cycle, Nutritional status, Adolescents, Irregular periods, SMAN 4 Blitar